2022
DOI: 10.1186/s13195-022-01000-z
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigured metabolism brain network in asymptomatic microtubule-associated protein tau mutation carriers: a graph theoretical analysis

Abstract: Background Studies exploring topological properties of the metabolic network during the presymptomatic stage of genetic frontotemporal dementia (FTD) are scarce. However, such knowledge is important for understanding brain function and disease pathogenesis. Therefore, we aimed to explore FTD-specific patterns of metabolism topology reconfiguration in microtubule-associated protein tau (MAPT) mutation carriers before the onset of symptoms. Methods S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Indeed, the mutations introduced in 3xTg-AD mice have been shown to alter metabolism and GSH levels. The MAPT P301L mutation has been shown using fluorodeoxyglucose-positron emission tomography (FDG-PET) to disrupt brain metabolism in pre-symptomatic human patients [ 61 ]. A reduction in GSH was observed in lymphoblasts with presenilin1 and AβPP mutations [ 62 ], and AβPP overexpression perturbed metabolism by decreasing mitochondrial respiration and enhancing glycolysis in SH-SY5Y cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the mutations introduced in 3xTg-AD mice have been shown to alter metabolism and GSH levels. The MAPT P301L mutation has been shown using fluorodeoxyglucose-positron emission tomography (FDG-PET) to disrupt brain metabolism in pre-symptomatic human patients [ 61 ]. A reduction in GSH was observed in lymphoblasts with presenilin1 and AβPP mutations [ 62 ], and AβPP overexpression perturbed metabolism by decreasing mitochondrial respiration and enhancing glycolysis in SH-SY5Y cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics, cognitive status, and linguistic and behavioral features of asymptomatic MAPT P301L carriers (a MAPT +), asymptomatic MAPT noncarriers (a MAPT –), bvFTD patients, and controls are shown in Table 1 . The demographic data of MAPT carriers and noncarriers have been previously reported [ 8 ]. There were no significant differences in age and sex between a MAPT + and a MAPT – groups or between bvFTD and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have specifically examined the associated changes in brain function with P301L mutations. One study reported hypometabolism of anterior cingulate gyrus in the preclinical stage in 6 MAPT P301L mutation carriers from 5 families [ 7 ], and we previously found that the metabolic network was altered with the insula as a reconfigured hub in patients with MAPT P301L mutations, suggesting complex functional alterations of insula before the onset of symptoms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous neuroimaging studies on bvFTD have revealed disruption of some topological properties, using modalities such as T1, resting-state functional magnetic resonance imaging, fluorodeoxyglucose positron emission tomography, and single-photon emission computed tomography to construct structural covariance, functional, or metabolic connectivity ( Agosta et al, 2013 ; Filippi et al, 2017 ; Liu et al, 2022 ; Malpetti et al, 2019 ; Ng et al, 2021 ; Nigro et al, 2021 ; Reyes et al, 2018 ; Saba et al, 2019 ; Sedeño et al, 2016 ; Sedeño et al, 2017 ; Vijverberg et al, 2017 ; Zhou et al, 2021 ). The brain structural covariance and functional networks of bvFTD patients showed preserved small-worldness organization but alterations in global network properties, such as lower average clustering coefficient, reduced global efficiency, and longer characteristic path length representing impairment in both the integration and segregation of information process ( Agosta et al, 2013 ; Nigro et al, 2021 ; Saba et al, 2019 ; Sedeño et al, 2016 ; Sedeño et al, 2017 ; Vijverberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the local level of the network, disruption of nodal metrics like nodal degree or local efficiency was reported, which was particularly predominant over frontal regions ( Agosta et al, 2013 ; Filippi et al, 2017 ; Malpetti et al, 2019 ; Sedeño et al, 2016 ). In addition, extensive reconfigurations of the nodes were observed in the bvFTD group ( Agosta et al, 2013 ; Liu et al, 2022 ; Malpetti et al, 2019 ; Zhou et al, 2021 ). However, few studies have correlated graph analysis metrics with clinical status, to explore the potential clinical relevance of network graph metrics ( Ng et al, 2021 ; Nigro et al, 2021 ; Reyes et al, 2018 ; Vijverberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%